Isothermal cold crystallization kinetics of borassus powder/poly(lactic acid) biocomposites - Marathe, Yogesh Nana; Chellaswamy, Ramesh; Badiger, Manohar Virupax (Polymer Crystallization, 2020)
Poly(lactic acid) (PLA) is an important bioplastic which is semicrystalline with very slow crystallization rate. Therefore, the processed PLA products are usually amorphous and transparent with low mechanical properties. Currently, research efforts are focused on enhancing the crystallization rate of PLA. In this work, natural borassus fibers are incorporated into PLA and the isothermal cold crystallization kinetics is investigated using differential scanning calorimetry and Avrami equation. The isothermal cold crystallization studies revealed that, the relative crystallinity increases with the increasing content of borassus. The Avrami exponent “n” was determined ~2.0 indicated the one‐dimensional crystal growth with rod‐like geometry. The overall crystallization rate increased due to the borassus content and was expressed by crystallization halftime (t1/2). This study clearly showed that borassus fibers act as nucleating agent.